Efektivitas Training dalam Mendukung Pengembangan SDM di Lingkungan PT. JNE Cabang Bandung: Studi Kualitatif tentang Peran Pelatihan dalam Peningkatan Kompetensi dan Kinerja Karyawan - Febrianti, Delia; Suhendi (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the effectiveness of training in supporting human resource development at PT. JNE Bandung Branch. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation study. The research informants consisted of HRD personnel and employees who had participated in training. The results of the study show that training contributes significantly to improving technical competence, work attitude, and employee motivation, which ultimately has an impact on improving individual and team performance. However, there are obstacles such as time constraints, uneven participation, and learning methods that are still dominated by lectures. This study confirms that training is an important strategy in human resource development, but it requires continuous evaluation and innovation, such as the application of blended learning and simulation-based training methods. The results of this study show that training has a significant contribution to human resource development. Training has been proven to improve technical competencies, such as skills in using tracking applications and package management systems, as well as soft skills, such as communication, customer service, and teamwork. In addition, training also encourages a positive work attitude and increases employee motivation and confidence in facing job demands. However, this study also found several obstacles in the implementation of training, including time constraints due to busy operations, learning methods that are still dominated by lectures, and uneven employee participation rates. Overall, this study confirms that training is an important strategy in supporting human resource development at PT. JNE Bandung Branch. To be more effective, the company needs to evaluate and innovate in the implementation of training, for example through the application of blended learning, increasing the interactivity of training methods with simulations and role plays, and more flexible scheduling. Thus, training can run more optimally and contribute directly to increasing the company's competitiveness.